Frequency of Measles Related Complications in Hospitalized Children - Farid Ullah, Taj Muhammad, Farman Ullah, Rida Naz, Bashir Khan, Shaista Qazi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Measles is a highly contagious viral infection, highly prevalent in children, clinically associated with complications of nervous, respiratory and digestive systems, with significant morbidity and mortality rate in the developing countries. Objectives: The study was aimed to determine the frequency of measles-related complications in hospitalized children. Methods: The study was conducted in tertiary care hospital of District Dera Ismail Khan, from February 2022 to November 2022, including 212 children affected with measles. Results: Most of the affected children (p<0.05) were infants of age group less than 2 years (45.28%), and males (63.67%) were at higher risk (p<0.05) as compared to the females (36.32%). Significantly higher proportion (p<0.05) of rural kids were affected with measles (58.96%) than urban. Most of the affected children (p<0.05) were not immunized (93.86%; 199/212), and the disease was significantly associated (p<0.05) with the nutritional, socioeconomic, immunization status of the patients. Different complications like pneumonia (31.13%), gastroenteritis (19.33%), conjunctivitis (17.45%), otitis media (7.07%) and encephalitis (2.35%), while 22.64% (42/212) were also observed and six of the 212 patients died of the infection. Conclusion: A huge proportion of patients contracted the disease due to the absence of vaccination measures and the disease was associated fatal secondary complications. Therefore, the government must encourage immunization against this extremely contagious but preventable infection in the children. Keywords: Complications; Encephalitis; Immunization; Measles; Pneumonia.